Trauma, truth, and testimony: analysing terrorism survivors’ victim impact statements - Farber, Shai (International journal of comparative and applied criminal justice, 2025)
Terrorism inflicts profound and enduring impacts on survivors and communities, yet the complex realities and needs of victims are often obscured in legal and policy discourses. This study examines the lived experiences of Israeli terrorism survivors through a qualitative thematic analysis of 28 victim impact statements submitted to courts from 2010 to 2023. The research uncovers the profound and enduring impact of terrorism on psychological, physical, social, and economic well-being. Pervasive grief, trauma, and irrevocable life changes emerge as central themes alongside the ripple effects on families and communities. Victims also describe daunting practical challenges in rebuilding their lives and express frustration with perceived leniency in sentencing and gaps in institutional support. While conveying urgent needs for comprehensive, trauma-informed assistance, the statements also reveal remarkable resilience and meaning-making in the face of horror. The article discusses the implications of developing more responsive, victim-centred policies and practices guided by the expressed priorities of survivors themselves. Key recommendations are outlined to foster a more humane and holistic response to the suffering of terrorism victims.